2017
DOI: 10.1016/j.neuro.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental neurotoxicity of inhaled ambient ultrafine particle air pollution: Parallels with neuropathological and behavioral features of autism and other neurodevelopmental disorders

Abstract: Accumulating evidence from both human and animal studies show that brain is a target of air pollution. Multiple epidemiological studies have now linked components of air pollution to diagnosis of autism spectrum disorder (ASD), a linkage with plausibility based on the shared mechanisms of inflammation. Additional plausibility appears to be provided by findings from our studies in mice of exposures from postnatal day (PND) 4-7 and 10-13 (human 3rd trimester equivalent), to concentrated ambient ultrafine (UFP) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
138
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 196 publications
(198 reference statements)
16
138
1
11
Order By: Relevance
“…Mice exposed developmentally to concentrated ambient UFP in our studies showed male-specific increases in IBA-1 in anterior commissure at postnatal day (PND) 14, and at PND55 in hippocampus (76, 77), and marked increases in corpus callosum when measured at PND270, regardless of whether exposure was during development, as adults, or both (58). Exposure of male rats to PM from pre-natal through adulthood increased cortical levels of the oxidative stress marker malondialdehyde and reduced levels of [superoxide dismutase]/[catalase] (60).…”
Section: Potential Mechanisms Of Cognitive Impairmentmentioning
confidence: 49%
“…Mice exposed developmentally to concentrated ambient UFP in our studies showed male-specific increases in IBA-1 in anterior commissure at postnatal day (PND) 14, and at PND55 in hippocampus (76, 77), and marked increases in corpus callosum when measured at PND270, regardless of whether exposure was during development, as adults, or both (58). Exposure of male rats to PM from pre-natal through adulthood increased cortical levels of the oxidative stress marker malondialdehyde and reduced levels of [superoxide dismutase]/[catalase] (60).…”
Section: Potential Mechanisms Of Cognitive Impairmentmentioning
confidence: 49%
“…Similarly, administration of UFP to male and female mouse pups from P4-13 led to a persistent increase in microglia number in males only, as far out as P270 [65]. Further there were changes in corpus callosum size and reduced myelination in males, and an excitatory-inhibitory imbalance in the frontal cortex in both males and females– consistent with many patients with autism [66,67].…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 75%
“…Studies assessing UFP exposure have shown various outcomes including oxidative stress, IL-1α and TNF- α expression in the brain [52], altered MAPK signaling, and elevated GFAP indicative of astrocyte activation in ApoE −/− mice [53]. Early postnatal exposure to UFP results in differential microglial responses dependent on sex and region of the brain, with some areas, such as the hippocampus, responding to UFP via increased microglial activation [31, 54], suggesting enhanced vulnerability to UFP exposure during neurodevelopment. UFP exposure exacerbates natural aging mechanisms in the brain via translocation to brain regions resulting in chronic neuroinflammation concurrent with neurodegenerative outcomes [5557].…”
Section: Discussionmentioning
confidence: 99%